Growth in high-value export markets in sub-Saharan Africa and its development implications - Maertens, Miet; Minten, Bart; Swinnen, Johan (Katholieke Universiteit Leuven, 2009)
During the past decades the global food system changed dramatically with increased trade in high-value food products, increased exports from developing countries, increased consolidation and dominance of large multinational food companies, and increased proliferation of public and private food standards. As a consequence, global food trade is increasingly organised around vertically coordinated supply chains rather than around spot market transactions. While there is consensus that these structural changes are profoundly changing the way food is produced and traded, there is no consensus on the overall welfare implications of increased high-value food exports and supply chain restructuring in poor countries. In this paper we discuss the income and poverty implications of expanded horticulture exports and changing supply chain structures for rural households in Sub- Saharan African exporting countries. We put together the economic arguments; distinguish different channels through which rural households are affected; provide evidence from three comparative case-studies on high-value horticulture exports; and derive implications for policy makers, private investors, and the development aid community.